1997
DOI: 10.1002/(sici)1097-4598(199711)20:11<1396::aid-mus7>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Value of sphincter electromyography in the diagnosis of multiple system atrophy

Abstract: It is clinically important, to distinguish between idiopathic Parkinson's disease (IPD) and multiple system atrophy (MSA) not only because of the implications for prognosis but also because urinary incontinence is often an early troublesome feature of MSA and by making the correct neurological diagnosis inappropriate urological surgery may be avoided. Onuf's nucleus in the sacral cord is the location of the anterior horn cells innervating the sphincters, and it is among central nervous system sites affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 0 publications
6
61
0
1
Order By: Relevance
“…However, some of these reports were published before a definition of MSA was established. Recent studies have reported almost normal EAS-EMG in patients with typical IPD 38,47,53,67 . Stocchi's study (1997) is important, since EMG in patients with IPD and MSA was performed by researchers blinded to the diagnosis.…”
Section: Idiopathic Parkinson's Disease (Ipd)mentioning
confidence: 95%
See 3 more Smart Citations
“…However, some of these reports were published before a definition of MSA was established. Recent studies have reported almost normal EAS-EMG in patients with typical IPD 38,47,53,67 . Stocchi's study (1997) is important, since EMG in patients with IPD and MSA was performed by researchers blinded to the diagnosis.…”
Section: Idiopathic Parkinson's Disease (Ipd)mentioning
confidence: 95%
“…Palace et al proposed that either of two criteria is sufficient to diagnose neurogenic changes in the EAS-EMG: (a) more than 20% of MUPs have a duration > 10 msec, or (b) the average duration of MUPs > 10 msec, particularly including the late components. 38 When satellite potentials were excluded, the duration of MUPs did not differ significantly between Parkinson's disease and MSA. 48 When lower motor neuron-type abnormalities are not apparent, it is reported that abnormal MUP recruitment pattern suggests pyramidal tract involvement.…”
Section: Methods and Interpretations Of Sphincter Emgmentioning
confidence: 99%
See 2 more Smart Citations
“…An external anal sphincter electromyogram [1] was performed. This was abnormal, demonstrating a severely depleted interference pattern and changes of chronic re-innervation.…”
Section: Case Historymentioning
confidence: 99%